P‐3.23: Multiple Regional‐Iteration Algorithm for Holographic Projection with Suppressed Speckle Noise - Guo, Min; Cai, Jiahao; Feng, Qibin; Wang, Zi; Lv, Guoqiang (SID International Symposium Digest of technical papers, 2022)
The spatial resolution of the holographic projection image is limited by the size of the spatial light modulator (SLM). Speckles noise always appear in the reconstructed image, which degrades the image quality. In this paper, a multiple regional iteration algorithm is proposed based on the GS algorithm to generate the hologram for holographic projection. More non‐sampling points can be controlled effectively. The spatial resolution of the reconstruction image can reach 8 times of the traditional one, and the speckle noise is suppressed at the same time. Compared with the traditional GS algorithm, the simulation results show that the root mean square error of the proposed algorithm reduces from 0.695 to 0.184, and the structural similarity index measure increases from 0.214 to 0.893.